Abemaciclib Inhibits Renal Tubular Secretion Without Changing Glomerular Filtration Rate. Issue 5 (30th December 2018) - Chappell, Jill C.; Turner, P. Kellie; Pak, Y. Anne; Bacon, James; Chiang, Alan Y.; Royalty, Jane; Hall, Stephen D.; Kulanthaivel, Palaniappan; Bonventre, Joseph V.
Abstract : Abemaciclib, an inhibitor of cyclin dependent kinases 4 and 6, is indicated for metastatic breast cancer treatment. Reversible increases in serum creatinine levels of 15–40% over baseline have been observed following abemaciclib dosing. This study assessed the in vitro and clinical inhibition of renal transporters by abemaciclib and its metabolites using metformin (a clinically relevant transporter substrate), in a clinical study that quantified glomerular filtration and iohexol clearance. In vitro, abemaciclib inhibited metformin uptake by organic cation transporter 2, multidrug and toxin extrusion (MATE)1, and MATE2‐K transporters with a half‐maximal inhibitory concentration of 0.4–3.8 μM. Clinically, abemaciclib significantly increased metformin exposure but did not significantly affect measured glomerular filtration rate, serum neutrophil gelatinase‐associated lipocalin (NGAL), serum cystatin‐C, or the urinary markers of kidney tubular injury, NGAL and kidney injury molecule‐1.